The impact of marketization on the communication of Chinese academicians: a genre analytical perspective. Issue 5 (19th October 2016) - Zhu, Hongqiang; Ren, Wei; Han, Zhengrui
ABSTRACT: Although the profound impact of marketization in academic world has been extensively studied, analytical attention is substantially concentrated on the organizational operation of universities. Less attention has been paid to the impact of marketization on the structure of academic disciplines and the communication of academicians, which is particular true in non-English-speaking countries. Drawing on the theory of genre analysis, this study sets out to investigate how the uptake of market discourse reshapes the structure of one Chinese academic discipline – the Chinese English Language Teaching (ELT) discipline, and how it redefines the pattern of Chinese ELT practitioners' disciplinary interaction. Textual data examined include textbooks, policy documents, curricula, syllabus, and insiders' accounts. Analytical results demonstrate that marketization is both a force driving the commercialization of Chinese ELT academic activities and a force facilitating the fragmentation of the formerly monolithic Chinese ELT discipline.